THE IMPLEMENTATION OF TEACHING LISTENING TOEFL AT TEST ENGLISH SCHOOL - Hayati, Faizatul; Kurniawan, Erwin Hari (Jurnal Pendidikan Bahasa Inggris Proficiency, 2022)
TOEFL test is requirement that must be done by some university, especially for English education department. From that situation, choose the right school to learn listening TOEFL. TEST English School is one of School or Course that focuses on the TOEFL preparation. This research conducted to describe the implementation of the TOEFL listening teachers at TEST English school in teaching TOEFL listening TOEFL. Descriptive qualitative method is used by this research. The data sources are the teachers of listening TOEFL, the director and 50 % students that learn listening TOEFL. Data collection technique in this research are interview, observation and documentation and three instrument there are interview guides, observation checklist and documentation. The data analysis technique in this research are reduction, data display and drawing conclusion. The result of this research are: 1) the teacher preparation in teaching listening TOEFL are syllabus, lesson plan and media, such as laptop, WhatsApp audio listening, projector, speaker, songs and Cambridge online dictionary, 2) the teachers do warming up before teaching, check the students’ homework, teaching by using clear explanation, good interaction with the students, solve the students’ problem, give the tips in doing the test and increase the students’ listening and give motivation to the students. 3) The evaluation done in every morning by doing test or scoring and done discuss the students’ problem in learning or doing the test in every Friday.